2018
DOI: 10.1085/jgp.201812137
|View full text |Cite
|
Sign up to set email alerts
|

Extracellular protons accelerate hERG channel deactivation by destabilizing voltage sensor relaxation

Abstract: hERG channels underlie the delayed-rectifier K+ channel current (IKr), which is crucial for membrane repolarization and therefore termination of the cardiac action potential. hERG channels display unusually slow deactivation gating, which contributes to a resurgent current upon repolarization and may protect against post-depolarization–induced arrhythmias. hERG channels also exhibit robust mode shift behavior, which reflects the energetic separation of activation and deactivation pathways due to voltage sensor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
37
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(47 citation statements)
references
References 82 publications
6
37
0
Order By: Relevance
“…Accessibility studies have also revealed that D460 and D509 stabilize the activated state (Liu et al, 2003), which is consistent with observations that neutralization of any of the acidic charges accelerates deactivation kinetics, likely by disrupting electrostatic interactions with S4 basic residues (Liu et al, 2003;Fernandez et al, 2005;Piper et al, 2008;Shi et al, 2014). Interestingly, disruption of the electrostatic pairing involving D509, either by protonation or alanine substitution, destabilizes the relaxed state of the voltage sensor leading to the loss of hysteresis and accelerated deactivation (Shi et al, 2019). This suggests that external acidic residues form stabilizing electrostatic interactions that are critical in recruiting the voltage sensor into the relaxed conformation and that these consequently control pore closure.…”
Section: The Voltage Sensor Domain (S1-s4)supporting
confidence: 82%
See 4 more Smart Citations
“…Accessibility studies have also revealed that D460 and D509 stabilize the activated state (Liu et al, 2003), which is consistent with observations that neutralization of any of the acidic charges accelerates deactivation kinetics, likely by disrupting electrostatic interactions with S4 basic residues (Liu et al, 2003;Fernandez et al, 2005;Piper et al, 2008;Shi et al, 2014). Interestingly, disruption of the electrostatic pairing involving D509, either by protonation or alanine substitution, destabilizes the relaxed state of the voltage sensor leading to the loss of hysteresis and accelerated deactivation (Shi et al, 2019). This suggests that external acidic residues form stabilizing electrostatic interactions that are critical in recruiting the voltage sensor into the relaxed conformation and that these consequently control pore closure.…”
Section: The Voltage Sensor Domain (S1-s4)supporting
confidence: 82%
“…The measured observation is that the voltage sensor required stronger repolarization to return to its resting position and to close the pore gate than was required to activate it ( Figure 3A). Similar hysteresis behavior has been reported in a broad collection of channels including sodium channels of the squid giant axon and NaChBac (Bezanilla et al, 1982;Kuzmenkin et al, 2004), calcium channels (Brum and Rios, 1987;Brum et al, 1988;Shirokov et al, 1992), potassium channels, such as KcSA (Tilegenova et al, 2017), Shaker (Haddad and Blunck, 2011;Lacroix et al, 2011;Labro et al, 2012;Priest et al, 2013), Kv1.2 (Labro et al, 2012), Kv3.1 (Labro et al, 2015), Kv7.2/7.3 (Corbin-Leftwich et al, 2016), Kv11.1 (hERG) (Piper et al, 2003;Tan et al, 2012;Hull et al, 2014;Goodchild et al, 2015;Thouta et al, 2017;Shi et al, 2019), Kv12.1 (Dierich et al, 2018), and HCN channels (Elinder et al, 2006;Bruening-Wright and Larsson, 2007). In HCN channels, the term mode-shift has been used to describe the hysteresis in the voltage-dependence of activation and deactivation in response to prolonged depolarization (Elinder et al, 2006), and the terms hysteresis and mode-shift are often used to describe the separation between the voltagedependence of Kv channel activation and deactivation.…”
Section: Hysteresis Of Gating In Voltage-dependent Ion Channelssupporting
confidence: 76%
See 3 more Smart Citations